Can Argentina's Experience Help Predict the Effects of a Potential Grexit? - Sebastian Dullien; Martin Rapetti; Pablo Schiaffino (Intereconomics, 2016)
In the debate about a possible exit of Greece from the euro area, Argentina is often referred to as an example–both by those in favour of and those warning of the adverse effects of a Grexit. Yet, while Argentina pulled off an impressive economic recovery after its 2001-02 crisis–one that goes beyond a mere commodity boom–there are important structural differences between the two countries, which still render a potential Grexit a very risky endeavour.
Keywords: 330; Wirtschaftskrise; Wirtschaftslage; Krisenmanagement; Vergleich; Argentinien; Griechenland; EU-Mitgliedschaft